Delineation of Fractured Aquifer Using Numerical Analysis (Factor) of Resistivity Data in a Granite Terrain - Rolland Andrade (International Journal of Geophysics)
In hard rock terrain, fractured aquifers comprise the major source of groundwater availability where the phreatic aquifer is desaturated. Identification of fracture zones in hard rock terrain and potential groundwater source delineation had been a perennial problem in hydrology. The purpose of this paper is to highlight the study over a small watershed area, in a granite terrain, wherein an attempt was made to delineate and map the fractured aquifer using numerical (factor) analysis of the conventional vertical electrical sounding data, which was obscure in curve matching technique. This numerical approach in concatenation with resistivity imaging or other techniques would prove to be an effective tool in groundwater exploration.